Sub-milliSievert (sub-mSv) CT Colonography: A Prospective comparison of image quality and polyp conspicuity at reduced dose versus standard dose imaging - Lubner, Meghan G. (Eur Radiol, 2015)
OBJECTIVE: To prospectively compare reduced-dose (RD) CT colonography (CTC) with standard-dose (SD) imaging using several reconstruction algorithms. METHODS: Following SD supine CTC, 40 patients (mean age, 57.3 years; 17 M/23 F, mean BMI, 27.2) underwent an additional RD supine examination (targeted dose reduction, 70–90%). DLP, CTDI(vol), effective dose, and SSDE were compared. Several reconstruction algorithms were applied to RD series. SD-FBP served as reference standard. Objective image noise, subjective image quality and polyp conspicuity were assessed. RESULTS: Mean CTDI(vol) and effective dose for RD series was 0.89 mGy (median 0.65) and 0.6 mSv (median 0.44), compared with 3.8 mGy (median 3.1) and 2.8 mSv (median 2.3) for SD series, respectively. Mean dose reduction was 78%. Mean image noise was significantly reduced on RD-PICCS (24.3±19HU) and RD-MBIR (19±18HU) compared with RD-FBP (90±33), RD-ASIR (72±27) and SD-FBP (47±14 HU). 2D image quality score was higher with RD-PICCS, RD-MBIR, and SD-FBP (2.7±0.4/2.8±0.4/2.9±0.6) compared with RD-FBP (1.5±0.4) and RD-ASIR (1.8±0.44). A similar trend was seen with 3D image quality scores. Polyp conspicuity scores were similar between SD-FBP/RD-PICCS/RD-MBIR (3.5±0.6/3.2±0.8/3.3±0.6). CONCLUSION: Sub-milliSievert CTC performed with iterative reconstruction techniques demonstrate decreased image quality compared to SD, but improved image quality compared to RD images reconstructed with FBP.